Low host specificity of root‐associated fungi at an Arctic site. Issue 4 (February 2014) - Botnen, Synnøve; Vik, Unni; Carlsen, Tor; Eidesen, Pernille B.; Davey, Marie L.; Kauserud, Håvard
Abstract In High Arctic ecosystems, plant growth and reproduction are limited by low soil moisture and nutrient availability, low soil and air temperatures, and a short growing season. Mycorrhizal associations facilitate plant nutrient acquisition and water uptake and may therefore be particularly ecologically important in nutrition‐poor and dry environments, such as parts of the Arctic. Similarly, endophytic root associates are thought to play a protective role, increasing plants' stress tolerance, and likely have an important ecosystem function. Despite the importance of these root‐associated fungi, little is known about their host specificity in the Arctic. We investigated the host specificity of root‐associated fungi in the common, widely distributed arctic plant species Bistorta vivipara, Salix polaris and Dryas octopetala in the High Arctic archipelago Svalbard. High‐throughput sequencing of the internal transcribed spacer 1 (ITS1) amplified from whole root systems generated no evidence of host specificity and no spatial autocorrelation within two 3 m × 3 m sample plots. The lack of spatial structure at small spatial scales indicates that Common Mycelial Networks (CMNs) are rare in marginal arctic environments. Moreover, no significant differences in fungal OTU richness were observed across the three plant species, although their root system characteristics (size, biomass) differed considerably. Reasons for lack of host specificity could be that association with generalist fungi may allow arctic plants to more rapidly and easily colonize newly available habitats, and it may be favourable to establish symbiotic relationships with fungi possessing different physiological attributes.